Mobility-aware placement of service-composed applications on Cloud-Edge Continuum - Albuquerque, Paulo R.; Koslovski, Guilherme P.; Pillon, Maurício A.; Ferreto, Tiago C. (Anais do International Symposium on Computer Architecture and High Performance Computing (SBAC-PAD), 2025)
The maturity of Cloud Computing (CC) and the advent of Edge Computing (EC) have paved the way to the concept of Cloud-Edge Continuum (CEC), where both of these domains are transparently available for applications to use. However, provisioning an application composed of many services in this Continuum can be challenging due to the dynamic nature of the environment, especially regarding the users’ geographical mobility. This requires a careful analysis from the perspectives of service providers, regarding application’s requirements and users’ Quality-of-Service (QoS) constraints. In this context, we propose, implement and analyze Mobility-aware Cloud-Edge Provisioning Heuristic (MCEPH), a mobility-aware orchestrator for placing service-composed applications atop CEC substrates. MCEPH relies on distances and delay metrics to dynamically provision services on CEC. In short, re-configurations are triggered to improve the overall performance perception of end users. For composing the simulation campaign, we developed a mobility model representing the citizens’ mobility in a Brazilian’s city. The model comprises points of interest, daily activity profiles, and multiple edge and cloud servers. The simulation campaign demonstrates how to configure MCEPH and discusses the overall benefits and drawbacks facing the specialized literature. Overall, the simulation campaign, aided by the more realistic mobility model, indicated great benefits to the users’ experienced quality of service from applications that fit the CEC pattern.